RASIO PERPUTARAN DAN PERIODE PENAGIHAN PIUTANG USAHA TERHADAP RASIO LANCAR PERUSAHAAN BARANG PRODUKSI - Roristua Pandiangan (University of Merdeka Malang, 2015)
The company ability to collect accounts and pay debt was one measurement of the company performance so thatthe company could survive in the market to serve the needs of consumers. This study aimed to reveal the effect ofthe company ability to collect accounts receivable to the company ability to pay short-term trade payables. Thisstudy used a descriptive research method with empirical studies approach. The population was 33 goods productioncompanies listed in the Indonesia Stock Exchange while the study samples were all study population. Theanalysis techniques used in this study were the accounts receivable turnover ratio, account receivables collectionperiod, current ratio, and multiple regression analysis. The results showed that: First, there was no partial effectof trade receivables turnover ratio to the current ratio at large trading company production of goods listed in theIndonesia Stock Exchange. Second, there was a partial effect of accounts receivable collection period to the currentratio at large trading company production of goods listed in the Indonesia Stock Exchange. Third, the accountsreceivable turnover ratio and accounts receivable collection period had a simultaneous effect to the current ratio atlarge trading company production of goods listed in Indonesia Stock Exchange.